2022
DOI: 10.1039/d2qo00676f
|View full text |Cite
|
Sign up to set email alerts
|

I2-Promoted site-selective C–C bond cleavage of aryl methyl ketones as C1 synthons for constructing 5-acyl-1H-pyrazolo[3,4-b]pyridines

Abstract: A novel iodine promoted [1 + 3 + 2] cleavage cyclization reaction for the synthesis of 1H-pyrazolo[3,4-b]pyridine from aryl methyl ketones, 5-aminopyrazoles and enaminones has been established. This transition metal-free...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…After a comprehensive consideration of those experimental results, we concluded that our transformation should not be a free radical-driven reaction. According to the present observations and literature existence [70][71][72][73][74] , a possible mechanism has been proposed in Fig. 5d, which was further supported by HRMS detection using acetophenone-D3 as a probe.…”
Section: Resultssupporting
confidence: 85%
“…After a comprehensive consideration of those experimental results, we concluded that our transformation should not be a free radical-driven reaction. According to the present observations and literature existence [70][71][72][73][74] , a possible mechanism has been proposed in Fig. 5d, which was further supported by HRMS detection using acetophenone-D3 as a probe.…”
Section: Resultssupporting
confidence: 85%
“…Additional experiments showed that the yield of 4a was decreased upon either increasing or decreasing the temperature from 100 °C (Table 1, entries 5 and 6). The addition of ZnCl 2 , FeCl 3 , HI, TFA and other acids was examined but none of these compounds was found to promote the reaction (Table 1, entries [7][8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…According to the research on enaminone, we found that enaminone can also be used as an equivalent of ethylene in this reaction system to give 2,3-diaroyl quinoline products. 59 In addition, this 1,4-dicarbonyl scaffold can be directly condensed with hydrazine hydrates to synthesize the pyridazino[4,5- b ]quinoline skeleton in one pot (Scheme 49). 60…”
Section: Application Of the I2–dmso Reagent System To Aryl Methyl Ket...mentioning
confidence: 99%